Transforming African Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Mr. Hon. Nyiira Mijumbi Zerubabel from the Ministry of Agriculture, Animal Industry and Fisheries of the Republic of Uganda talks about agriculture, commercial farming and peasant income. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/